2014
DOI: 10.1021/ac4038398
|View full text |Cite
|
Sign up to set email alerts
|

Angle-Tunable Enhanced Infrared Reflection Absorption Spectroscopy via Grating-Coupled Surface Plasmon Resonance

Abstract: Surface enhanced infrared absorption (SEIRA) spectroscopy is an attractive method for increasing the prominence of vibrational modes in infrared spectroscopy. To date, the majority of reports associated with SEIRA utilize localized surface plasmon resonance from metal nanoparticles to enhance electromagnetic fields in the region of analytes. Limited work has been performed using propagating surface plasmons as a method for SEIRA excitation. In this report, we demonstrate angle-tunable enhancement of vibrationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Even thicker PMMA films with thicknesses between 30 and 300 nm were used in the work of Petefish and Hillier to reveal the SEIRS characteristics of a grating fabricated by laser interference lithography [94] (see Figure 7B). As a result, these gratings, subsequently covered with silver, show a sinusoidal surface profile with a maximum height of 100 nm (3025 nm pitch) and 300 nm (1710 nm pitch).…”
Section: Gratingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even thicker PMMA films with thicknesses between 30 and 300 nm were used in the work of Petefish and Hillier to reveal the SEIRS characteristics of a grating fabricated by laser interference lithography [94] (see Figure 7B). As a result, these gratings, subsequently covered with silver, show a sinusoidal surface profile with a maximum height of 100 nm (3025 nm pitch) and 300 nm (1710 nm pitch).…”
Section: Gratingsmentioning
confidence: 99%
“…The authors found by calculation that a reflectance signal of more than 5% should be possible if a maximum imaginary dielectric permittivity of 3 at the molecular resonance was assumed. For the assumed thickness of 1 nm, this would be an enormous signal, but the simulation does not take into account that the strongest imaginary dielectric permittivity for an organic material in the infrared spectral range (caused by the C = O stretching vibration) is not higher than about 1.5 [94]. For proteins, it seems that the corresponding vibrations that involve the C = O stretching vibrations (amide I and II) are even weaker and do not show values above 1 [144].…”
Section: Graphenementioning
confidence: 99%
“…The second issue is related to the dynamical tunability of the PFR. It is known that if the vibrational modes of the molecules is far away from a plasmonic resonance, the signal from the molecular vibrational absorption (relating with the absorption cross section) will be significantly decreased . Therefore, the resonant wavelength of nanostructure has to be tuned.…”
Section: Introductionmentioning
confidence: 99%
“…This RI sensitivity allows for high throughput label free sensing/diagnostics [26][27][28][29][30][31] and thin film deposition tracking. [32][33][34][35][36][37][38][39][40] Additionally, because SPR peak shift can be tracked versus time, kinetics and binding affinity can be elucidated. 19,41,42 The first commercial SPR instrument for binding affinity was sold in 1990 under the name of BIACORE.…”
Section: Surface Plasmon Resonance Interests and Application Fieldsmentioning
confidence: 99%
“…Additionally, the enhanced electric field associated with the resonance mode can be matched to atomic or molecular resonance Spectroscopic techniques enhanced by SPR include Surface Enhanced Raman Spectroscopy (SERS), 34,[46][47][48][49][50] Surface Enhanced Infrared Absorption (SEIRA), 36,47,51,52 and SPR enhanced fluorescent signaling. [53][54][55][56][57][58][59][60][61] SPR also plays an integral role in near-field imaging techniques.…”
Section: Surface Plasmon Resonance Interests and Application Fieldsmentioning
confidence: 99%